2010
DOI: 10.1111/j.1365-2664.2010.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural intensification on plant diversity in Mediterranean dryland cereal fields

Abstract: Summary1. Agricultural intensification, at field and landscape scales, has caused a decrease in weed richness and changes in species composition. In order to prevent this loss of diversity and develop efficient management regimes, it is important to understand how both aspects of intensification affect plant diversity and the way in which they interact. 2. This study assessed plant diversity at the centre, edges and boundaries of 29 organic and 29 conventional cereal fields distributed in 15 agrarian localitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 44 publications
10
92
0
5
Order By: Relevance
“…Several studies have shown that the intensification of crops, due to the availability of irrigation, leads to a decrease in biodiversity (Storkey and Westbury, 2007;José-María et al, 2010;Plaza et al, 2011;Sans et al, 2013). However, in the present study, an increase of total plant diversity was observed.…”
Section: As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the intensification of crops, due to the availability of irrigation, leads to a decrease in biodiversity (Storkey and Westbury, 2007;José-María et al, 2010;Plaza et al, 2011;Sans et al, 2013). However, in the present study, an increase of total plant diversity was observed.…”
Section: As Shown Inmentioning
confidence: 99%
“…Furthermore, weeds are able to survive and grow in different ecological habitats, with their occurrence being very sensitive to changes in agricultural practices (Fried et al, 2010;Petit et al, 2011). New agricultural management practices lead to new balances and such information is considered to be of major importance (José-María et al, 2010;Sans et al, 2013). Ecological services that this type of vegetation provides to the agro-ecosystems are not negligible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important aspect has to do with the fact that the intensification of agricultural systems leads to a loss of plant biodiversity (Storkey & Westbury, 2007;Stoate et al, 2009;José-Maria et al, 2010;Sans et al, 2013), which threatens the sustainability of the services provided by a current and modern agriculture. Also, the effect of climate change on organisms and on their geographical distribution (Walther et al, 2002) may influence this dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, arable weeds have suffered a severe decline over all Europe, which has developed concerns over the sustainability and environmental consequences of the intensification of land use in agricultural systems [12]. Plant diversity in dry land Mediterranean cereal fields is affected by agricultural intensification at any of these abovementioned scales, as reflected by a decrease of plant species richness and changes in species composition [13]. But the ecological implications of these changes still remain uncertain, because in such agro systems there is a high variability in the local occurrence of plant species [14,15].…”
Section: The Weed Problem On Cereal Arable Fieldsmentioning
confidence: 99%